2008
DOI: 10.1111/j.1572-0241.2008.01989.x
|View full text |Cite|
|
Sign up to set email alerts
|

3-Yr-Follow-Up of Topical Corticosteroid Treatment for Eosinophilic Esophagitis in Adults

Abstract: It appears that EE is a chronic remitting disorder that requires more than one topical steroid treatment course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 42 publications
0
79
0
5
Order By: Relevance
“…Notably, in the systematic review and meta-analysis conducted by Chuang et al [136], the significant efficacy of topical steroid therapy was observed only in patients with prior PPI therapy (PPI non-responders); this indicates the usefulness of the PPI trial prior to steroid therapy. Maintenance therapy by topical steroids is effective for controlling the clinical symptoms or eosinophilic inflammation in some patients [134,137]; however, its withdrawal leads to relapse at a high rate [73,138,139].…”
Section: Drug: Steroid Therapymentioning
confidence: 99%
“…Notably, in the systematic review and meta-analysis conducted by Chuang et al [136], the significant efficacy of topical steroid therapy was observed only in patients with prior PPI therapy (PPI non-responders); this indicates the usefulness of the PPI trial prior to steroid therapy. Maintenance therapy by topical steroids is effective for controlling the clinical symptoms or eosinophilic inflammation in some patients [134,137]; however, its withdrawal leads to relapse at a high rate [73,138,139].…”
Section: Drug: Steroid Therapymentioning
confidence: 99%
“…Cependant, cette dernière observation pourrait être due aux critères d'évaluation, à la population choisie et à un fort effet placebo.L es corticoïdes permettent aussi, chez les patients qui répondent, d'obtenir une normalisation du profilh istologique [70,71], et possiblement un remodelage oesophagien si le traitement est prolongéà50 semaines [72]. Les corticoïdes administrés par voie locale peuvent entraîner des effets secondaires locaux tels que des infections à Candida [70], les patients rechutent le plus souvent à l'arrêtd ut raitement et si l'administration de corticoïdes est prolongée, une partie des patients perd le bénéfice clinique et histologique du traitement [72,73]. Si on considère aussi une étude rétrospectivep ortant sur 221 patients souffrant d'EoE traitésa ux corticoïdes et montrant que seulement 57 %a vaient une réponse histologique en première intention [74], on s'aperçoit que les corticoïdes ne représentent pas la panacéep our le traitement de l'EoE, à l'image des allergies respiratoires.…”
Section: Prise En Charged El 'Eoeunclassified
“…A recent meta-analysis of topical steroids in placebo controlled trials support the idea that these medicines provide prompt and significant histological response but that symptom relief is less reliable [98].…”
Section: Topical Glucocorticoidsmentioning
confidence: 99%